Avoiding a red card: recommendations for a consistent standard of concussion management in professional football (soccer) - Gouttebarge, V.; Goedhart, E. A.; Orhant, E.; Patricios, J. (British Journal of Sports Medicine, 2022)
Compared with some collision/contact sports, concussions are relatively uncommon in professional football (soccer).1 2 Nevertheless, professional football has been under repeated scrutiny because of questionable recognition and management (on-field and off-field) of concussions during several high-profile international and national competitions. Given the Concussion in Sport Consensus process has been ongoing for two decades, it is important that professional football adopt consistent policies that represent the highest standard of concussion care.1 We believe the current approach to concussion in some professional football competitions may warrant a red card. Being the world`s highest profile sport, we acknowledge that football`s apparent concussion management oversights may appear to be disproportionately exposed in both the medical and public eye. We also recognise that the Fédération Internationale de Football Association (FIFA) and many professional leagues have made many steps towards promoting high-quality concussion care. Equally, however, variable policies exist that may compromise athlete care, and the sports profile and popularity should be used to promote optimal concussion care and educate millions. As clinicians who have been working in professional football for over 100 cumulated years, we propose a series of measures to improve the recognition and management of concussion across professional football.